Histology and Glycoconjugates Histochemistry in the Small and Large Intestinal Epithelium of the Malayan Pangolin, Manis javanica - Suprasert, Apinun; Liumsiricharoen, Maleewan; Pongket, Pakawadee; Prapong, Teerasak; Doungern, Apantree; Prompa, Nathanan (Agriculture and Natural Resources, 2007)
Histology and glycoconjugates histochemistry in the small and large intestinal epithelium of the Malayan Pangolin (Manis javanica) were studied by means of histological and histochemical techniques. The staining procedures employed were Hematoxylin-Eosin (H&E), Alcian Blue (AB) pH 2.5, Periodic Acid-Schiff (PAS), AB pH 2.5-PAS and lectin including penut agglutinin (PNA), Ulex europeus agglutinin-I (UEA-I), wheat germ agglutinin (WGA) and Maackia amurensis (MAL-II). The intestinal canal displayed no divivsion between small and large intestine, other than a continuous enlargement, and there was no cecum. The mucous membrane of the pangolin small intestine was thrown into high villi and long crypt of Lieberkuhn. While, the mocosa of large intestine lied in a series of irregular fold, not villi. The mucosa of both intestine was covered by simple columnar epithelium in which 2 type of cells were encountered columnar and goblet cells. The mucous granule of goblet cells in small intestine were found to contain primarily neutral glycoconjugates with galactose and sialic acid residues. On the contrary, the mucous epithelium of large bowel involved predominantly acid sulfated glycoconjugates with N-acetylglucosamine, fucose and sialic acid residues. Furthermore, the nature of glycoconjugates in mucous epithelium of both intestine was found to change during the upward migration from deep to superficial part.